2020
DOI: 10.1007/s00408-020-00393-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Serum Interleukin 6 and Surfactant Protein D Levels Associated with the Clinical Course of COVID-19?

Abstract: Purpose SARS-CoV-2 (COVID-19) has infected more than 7 million people worldwide in the short time since it emerged in Wuhan, China in December 2019. The aim of this study was to investigate the relationship between serum interleukin 6 (IL-6) and surfactant protein D (SP-D) levels and the clinical course and prognosis of COVID-19. Materials and Methods The study included a total of 108 individuals: 88 patients who were diagnosed with COVID-19 by real-time PCR of nasopharyngeal swab samples and admitted to the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 26 publications
5
68
3
1
Order By: Relevance
“…Similarly, SP‐D levels increase in respiratory distress syndromes triggered by septic shock as well as in patients affected by severe COVID‐19 alveolar disruption [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SP‐D levels increase in respiratory distress syndromes triggered by septic shock as well as in patients affected by severe COVID‐19 alveolar disruption [24].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in vascular permeability causes fluid accumulation in lung tissue and the interstitial area, resulting in an acute setting of respiratory failure. Positive results have been reported that IL-1 and IL-6 antagonists can be used to control this setting 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of SP-D have been found to be elevated in severe acute respiratory syndrome (SARS)-related pneumonia, potentially through leakage from the damaged lung into the blood ( 40 ). Furthermore, recent studies have shown that COVID-19 patients who went on to develop macrophage activation syndrome had significantly higher serum levels of SP-D on admission and that SP-A and SP-D serum levels correlated with more severe COVID-19 disease ( 41 , 42 ). Thus, early work suggests a role for SP-D in SARS-CoV-2 infection, which may modulate infection and the pathologic host inflammatory response.…”
Section: Anti-viral Functions Of Sp-a and Sp-dmentioning
confidence: 99%